Impact of an Educational Intervention on Public Perception of Health Problems in Brachycephalic Dogs - Gareth Smith; Alison P. Wills (Veterinary Medicine and Science)
ABSTRACT Background The popularity of brachycephalic dog breeds has increased over the last decade despite their numerous health issues. The continued popularity of these breeds raises questions about public understanding and perception of their health problems. Objectives This study aimed to determine the impact of a minimalist educational intervention on public awareness of the health of brachycephalic breeds and attitudes to breeding practices. Methods Data were collected via an online questionnaire that assessed awareness of health issues and attitudes to breeding brachycephalic breeds before and after an educational intervention. The intervention consisted of a factsheet that survey participants were required to read. Kruskal–Wallis tests were used to test for an effect of dog ownership status (dog owner, owner of a brachycephalic breed, or not a dog owner) on perceptions, and Wilcoxon signed‐rank tests were used to test for the effect of the intervention on the perceptions of each individual group. Results There were 141 survey responses obtained from owners of brachycephalic breeds (n = 41), owners of other breeds (n = 88), and non‐dog owners (n = 12). The intervention significantly improved the awareness of breed‐related health issues in owners of non‐brachycephalic breeds (p < 0.001) and non‐dog owners (p = 0.016) but not in owners of brachycephalic dogs (p = 0.581). Owners of non‐brachycephalic breeds significantly reduced their support for breeding brachycephalic dogs following the intervention (p < 0.001), but there was no significant effect on participants who did not own a dog (p = 0.059) or who owned a brachycephalic breed (p = 0.359). Conclusions This study has demonstrated that education can change public perception of breed‐specific health issues and attitudes to continued breeding of brachycephalic dogs. However, attitudes of owners of these breeds appear to be less easily influenced than people who do not already own these dogs. Therefore, further work is needed to understand the motivations for breed ownership and the continued popularity of brachycephalic dogs.